Explorations in African History: Reading Patrick Harries : Reading Patrick Harries - Schmid, Pascal; Bishop, Stephanie; Arlt, Veit (Book collections on Project MUSE., 2015)
This collection of essays documents the growth of African history as a discipline at the University of Basel since 2001. It thus pays tribute to fourteen years of research and teaching by Patrick Harries at the Department of History and the Centre for African Studies Basel. The Festschrift covers a broad range of topics from mine labour to missionary endeavour and the production of knowledge, reflecting some of his core research interests. The contributions engage with Patrick Harries' oeuvre with reference to the authors' own scholarship or vice-versa. Some directly address his publications while others take his teaching, correspondence, remarks or intellectual life more broadly as a point of reference. They all pay tribute to a brilliant and inspiring scholar, a great teacher and a kind person.